El péndulo de las identidades católicas: oscilaciones entre representaciones colectivas y reconocimiento institucional - Renée de la Torre (Estudios sobre las Culturas Contemporáneas)
Guadalajara´s Catholic Church is a complex institution housing diverse forms of religious activism, each subject to different types of institution recognitioa The study of the identities of the laity requires the methodologically outlining of the I-us-others representation within the fields of interaction. The straggle within Catholicism occurs precisely in this intersection between frames of reference and belonging to groups based on direct contact and ideological agreement.